Attentional Bias to Negative Emotion as a Function of Approach and Withdrawal Anger Styles: An ERP Investigation - Stewart, Jennifer L. (2010)
Although models of emotion have focused on the relationship between anger and approach motivation associated with aggression, anger is also related to withdrawal motivation. Anger-out and anger-in styles are associated with psychopathology and may disrupt the control of attention within the context of negatively valenced information. The present study used event-related brain potentials (ERPs) to examine whether anger styles uniquely predict attentional bias to negative stimuli during an emotion-word Stroop task. High anger-out predicted larger N200, P300, and N400 to negative words, suggesting that aggressive individuals exert more effort to override attention to negative information. In contrast, high anger-in predicted smaller N400 amplitude to negative words, indicating that negative information may be readily available (primed) for anger suppressors, requiring fewer resources. Individuals with an anger-out style might benefit from being directed away from provocative stimuli that might otherwise consume their attention and foster overt aggression. Findings indicating that anger-out and anger-in were associated with divergent patterns of brain activity provide support for distinguishing approach- and withdrawal-related anger styles.